Current Topics in Tropical Emerging Diseases and Travel Medicine 2018
DOI: 10.5772/intechopen.78981
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Tropical Diseases with an Impact on Kidney Function

Abstract: Neglected tropical diseases are a group of infectious diseases caused by infectious and parasitic agents that occur in a large part of the world affecting millions of people and can complicate matters with serious organ damage. The kidneys can be affected in many of these diseases, including Chagas disease, dengue, leishmaniasis, leprosy, and schistosomiasis. In this chapter, we describe the mechanisms by which the kidneys are damaged in the setting of these diseases, the clinical manifestations, and the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…Lesi ginjal yang berbeda telah dijelaskan pada kusta, termasuk glomerulonefritis akut dan kronis, nefritis interstitial, amiloidosis sekunder, dan pielonefritis. Mekanisme pasti patologi terjadinya CKD pada kusta tidak sepenuhnya dipahami (6). Keterlibatan ginjal pada kusta dapat berkembang menjadi penyakit ginjal stadium akhir (ESRD) dan oleh karena itu dapat menjadi penyebab penting kematian pada pasien kusta (8).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Lesi ginjal yang berbeda telah dijelaskan pada kusta, termasuk glomerulonefritis akut dan kronis, nefritis interstitial, amiloidosis sekunder, dan pielonefritis. Mekanisme pasti patologi terjadinya CKD pada kusta tidak sepenuhnya dipahami (6). Keterlibatan ginjal pada kusta dapat berkembang menjadi penyakit ginjal stadium akhir (ESRD) dan oleh karena itu dapat menjadi penyebab penting kematian pada pasien kusta (8).…”
Section: Pembahasanunclassified
“…Pada pasien anemia berat, berdasarkan konsentrasi hemoglobin darah, transfusi darah lengkap dilakukan agar kondisi lebih stabil sebelum menerima pengobatan MDT (11). Pasien CKD dapat menerima MDT, namun pada pasien dengan ESRD dan kustas, selain menerima pengobatan MDT, diperlukan terapi pengganti ginjal seperti hemodialisis atau transplantasi ginjal, serta dialisis pada pasien kusta-ESRD tidak mengganggu respon terapi MDT pada kusta (6).…”
Section: Pembahasanunclassified
“…S. mansoni-related renal morbidity is a result of the disease of the host cell-mediated granulomatous immune response to the antigens of the parasite eggs trapped in the tissue [11] [12]. Studies have demonstrated that the association of S. mansoni and renal dysfunction can be explained by the deposition of immune complexes formed by Schistosoma antigen and IgG/IgM antibodies in the glomerular basement membrane, leading to glomerulonephritis [13] [14]. Chronic infection of S. mansoni in children may lead to long-standing proteinuria, which can eventually cause chronic kidney disease and hypertension later in life [9] [10].To date, PZQ administered at the standard single oral dose of 40 mg/kg body weight is the mainstay drug recommended by WHO for chemo-preventive therapy [15] [16] [17].…”
Section: Introductionmentioning
confidence: 99%